2019
DOI: 10.1002/fsn3.938
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of appetite‐regulating hormones of mother–infant dyad according to the type of feeding

Abstract: Satiety and appetite‐stimulating hormones play a role in the regulation of food intake. Breastfed infants may have a different profile of serum appetite‐regulating hormones than formula‐fed infants. We propose to demonstrate that the serum concentration of appetite regulatory hormones differs according to the type of feeding and that there is a correlation between the serum concentrations of these hormones in mothers and in infants at 4 months of age. In a cross‐sectional analysis, 167 mother–newborn dyads at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…In the case of ghrelin, a potent orexigenic, its concentration in infants appears to be more related to the need to be fed and nourished properly. The higher concentration of GLP‐1 and peptide YY is the result of regulatory mechanisms related both to body composition and to the infant's own growth needs (Vasquez‐Garibay et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of ghrelin, a potent orexigenic, its concentration in infants appears to be more related to the need to be fed and nourished properly. The higher concentration of GLP‐1 and peptide YY is the result of regulatory mechanisms related both to body composition and to the infant's own growth needs (Vasquez‐Garibay et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The collection of blood samples and the assays for the determination of hormonal biomarkers are described elsewhere (Vasquez‐Garibay et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that compare the postprandial hormone release in infants following consumption of human milk vs IMF are limited in number but do confirm differences depending of feeding mode (Lucas et al, 1981;Salmenpera et al, 1988;Slupsky et al, 2017). Recent studies also showed that the profiles of fasting state appetite regulating hormones including insulin and leptin were different between breast-and formula-fed infants (Breij et al, 2017;Vasquez-Garibay et al, 2019). Moreover, these hormones have associated with brain development and cognitive function (Plagemann et al, 2005;Farr et al, 2015;Cato and Hershey, 2016).…”
Section: The Physical Properties Of Lipids and Lipid Globulesmentioning
confidence: 99%